Shaping the future of medical laboratory practices in Somaliland: a review of the current standards - Omar Abdulkarim Saeed Alhammadi; Zhinya Kawa Othman; Ephraim Ikpongifono Udokang; Tayaba Sarfraz; Olalekan John Okesanya; Jerico Bautista Ogaya; Don Eliseo Lucero-Prisno (Discover Applied Sciences)
Abstract Medical laboratory science has an acknowledged pivotal role in evidence-based practices and patient-centered care, informing clinical decision-making for precise diagnosis and treatment. Laboratory practices’ advancements in sub-Saharan Africa indicate several challenges and limitations, where progress remains slow, hindered by limited accredited laboratories, weak governance, and inadequate national health policies. This review presents the current status of medical laboratory practices in Somaliland, emphasizes the urgent need for reform and adherence to international standards, and provides actionable recommendations for transforming the healthcare system. While strides have been made toward aligning laboratory practices with international standards, inadequate compliance underpins challenges in Somaliland’s medical laboratory practices, highlighting suboptimal management performance and the urgent need for adherence to international benchmarks that fit Somaliland's laboratory landscape and the gap that pertains. This review discusses the Total quality management (TQM) approach, emphasizing a dual focus on quality of management and management of quality, which is vital for ensuring reliable, high-quality services. While compliance with international standards demonstrates significant outcomes, quality management is the key role guiding this compliance and ensuring service quality. Findings demonstrate that quality management and efficient leadership are critical for a successful pre-accreditation and post-accreditation process, indicating the dual focus as the main strategy to ensure Somaliland’s medical laboratories meet global standards of excellence in terms of diagnostic accuracy, operational efficiency, patient outcomes, resilience and sustainability. Finally, effective compliance with international benchmarks that promote the quality management and management of quality standards can ensure the implementation of the dual focus and maintain TQM. International collaboration are necessary for knowledge sharing, resources, and guidance as current practices’ data and information available. Consultation for effective compliance is highly recommended to navigate the challenges of simultaneously considering and implementing the proposed dual focus to obtain accreditation. It promotes continuous evaluation to achieve the targeted improvements and growth.